Uma Heurística ILS para Resolução do Problema de Carregamento e Descarregamento de Contêineres em Navios Porta-contêineres - de S. Neto, Amaro José; Vianna, Dalessandro S.; D. Vianna, Marcilene de Fátima (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2011: Anais do VII Simpósio Brasileiro de Sistemas de Informação, 2011)
When docking at a port terminal it may be necessary to perform various operations of loading and unloading containers. Sometimes, when unloading, the target container which needs to be unloaded may be positioned below other containers that will not be unloaded at this time. These ones need to be removed to unload the target container. The goal is to find the best loading sequence minimizing thus the number of "rearrangements". The proposed heuristic was compared with a greedy heuristic and a local search method. The results show the adequacy of ILS heuristic to the problem addressed.